A Case Study of Hypnotic Anesthesia in Breast Lump Surgery - Mehdi Pourasghar; Mitra Moslehi Jouybari; Fatemeh Moslehi Jouybari; Meisam Kord (Mashhad University of Medical Sciences, 2023)
Introduction: Breast cancer is the most important and common disease among women, which has the second highest death rate after lung cancer. Considering that the breast mass has no medical treatment and its definitive treatment is surgery and the side effects caused by drug anesthesia are high, so using hypnotic anesthesia is a good way to reduce the effects caused by anesthesia, faster healing the injury and reducing the length of hospital stay. Therefore, considering the benefits of using hypnosis in breast surgery, this research was conducted as a case study of hypnotic anesthesia in breast lump surgery.Case presentation: In this case study, which used non-drug treatment (psychotherapy) i.e. hypnotic anesthesia to prevent the side effects of medical anesthesia, the investigated sample was a 45-year-old woman who was admitted to a hospital in Sari after diagnosed with a breast mass and was discharged from the hospital in a good condition a few hours after the partial mastectomy. Hypnosis was performed by an experienced psychiatrist and psychotherapy fellowship in the Scientific Association of Clinical Hypnosis of Iran. The patient underwent direct surgery by hypnotic anesthesia and after the completion of the surgery, which took about 30 minutes, using direct induction of hypnosis, the patient regained full consciousness and left the hospital a few hours after the operation in a good mood.Conclusion: Considering the many surgical operations and the benefits of hypnosis, it is recommended to provide the conditions for using this method according to the nature of the treatment.